2017
DOI: 10.1101/139113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Untargeted metabolomic analysis in naturally occurring canine diabetes mellitus identifies similarities to human Type 1 Diabetes

Abstract: While predominant as a disease entity, knowledge voids exist regarding the pathogenesis of canine diabetes. To test the hypothesis that diabetic dogs have similar metabolomic perturbations to humans with type 1 diabetes (T1D), we analyzed serum metabolomic profiles of breed-and body weightmatched, diabetic (n = 6) and healthy (n = 6) dogs by liquid chromatography-mass spectrometry (LC-MS) profiling. We report distinct clustering of diabetic and control groups based on heat map analysis of known and unknown met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Since saliva is rich in small molecules and given its role as “a mirror of the body”, there is a growing interest towards saliva usage as a non-invasive sample material for monitoring health trajectories to aid diagnosis or reveal the molecular mechanisms of disease pathologies. The same applies to domestic dogs which suffer from similar diseases to humans such as metabolic diseases, chronic inflammation, and cancers, manifested as diabetes (O'Kell et al 2017 ), inflammatory bowel disease (Minamoto et al 2015 ) and leukemia (Breen and Modiano 2008 ), respectively. Physiological similarity with humans and the large size of the canine have been reasons for the rise of these animals to one of the biomedical models alongside the rodents, for example in the study of genomics (Hytonen and Lohi 2016 ; van Steenbeek et al 2016 ) and behavior (Puurunen et al 2018 ).…”
Section: Introductionmentioning
confidence: 97%
“…Since saliva is rich in small molecules and given its role as “a mirror of the body”, there is a growing interest towards saliva usage as a non-invasive sample material for monitoring health trajectories to aid diagnosis or reveal the molecular mechanisms of disease pathologies. The same applies to domestic dogs which suffer from similar diseases to humans such as metabolic diseases, chronic inflammation, and cancers, manifested as diabetes (O'Kell et al 2017 ), inflammatory bowel disease (Minamoto et al 2015 ) and leukemia (Breen and Modiano 2008 ), respectively. Physiological similarity with humans and the large size of the canine have been reasons for the rise of these animals to one of the biomedical models alongside the rodents, for example in the study of genomics (Hytonen and Lohi 2016 ; van Steenbeek et al 2016 ) and behavior (Puurunen et al 2018 ).…”
Section: Introductionmentioning
confidence: 97%
“…3hydroxy derivatives of MCFAs are derived from endogenous and exogenous sources. Although basal plasma concentrations of 3-hydroxyoctanoic acid (3HO) and 3-hydroxydecanoic acid (3HDec) rarely exceed 0.4 μM, they are both increased in patients undergoing a ketogenic diet and in patients with diabetic ketoacidosis or defects of mitochondrial β-fatty acid oxidation [5,11,18,19]. 3-hydroxy fatty acids of 10-14 carbon chain lengths are also components of lipopolysaccharides (LPS) of Gram-negative bacteria and have been used as endotoxin markers in clinical and environmental samples [20][21][22][23].…”
mentioning
confidence: 99%
“…Similarly, a 2017 study identified similar serum metabolites in canine diabetes mellitus and human type I diabetes, including changes in glycolytic intermediates and elevated levels of branch-chain amino acids. 51 Reflecting the increasingly recognized importance of the microbiome, multiple studies explored the relationship between host health and the gastrointestinal microbiota. 22,44 As an example, dogs with acute diarrhea were found to have decreased fecal concentrations of Faecalibacterium spp.…”
Section: Principal Findingsmentioning
confidence: 99%